Gamification-Based Discovery Learning: Impact on Biology Students' Cognitive Outcomes and Motivation - Salma Azzah Fitran Saputri; Suranto Suranto; Alanindra Saputra (Universitas Sebelas Maret, 2026)
This study aimed to investigate the impact of a gamification-based learning model on learning outcomes and student learning motivation in ecosystem materials, as well as to explore the relationship between learning motivation and learning outcomes. A quasi-experimental pretest-post test non-equivalent control group design was used. The subjects were tenth-grade high school students selected using the cluster random sampling. Data was collected using validated tests and questionnaires and analyzed using ANCOVA and Pearson Product-Moment correlation tests. Hypothesis testing was done with the ANCOVA test and the Pearson Product-Moment correlation test. The results showed that the gamification-based discovery learning model had a significant effect on both learning outcomes (sig. = 0.028) and learning motivation (sig. = 0.00) with a moderate effect size. Furthermore, a strong positive correlation was also identified between learning motivation and learning outcomes after the application of the model. This research concludes that the integration of gamification elements into the discovery learning model is an effective pedagogical approach for fostering student motivation and improving academic achievement in secondary education.